Implementasi Metode Analytical Hierarchy Process (AHP) dalam Pemilihan Supplier Coolant di PT. ABC - Bernadeta, Deviana Nauli; Fasa, Nadia (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
Suppliers act as suppliers of main materials and other additional materials to help with the production process. To get the right supplier, the company selects several suppliers who have product criteria that match the company's needs. So far, supplier selection has been carried out by PT. ABC only uses intuition based on experience working with the supplier and the prices offered. In this incident, a method was proposed that could assist in selecting suppliers according to PT's needs. A B C. An effective way to choose a supplier is to use a decision support system, so that you get the right supplier according to your needs. The Analytical Hierarchy Process (AHP) method is one method that can be applied. This method is used by weighting the criteria and sub-criteria. The research results found that quality criteria were priority criteria with a weight of 0.380. Sub criteria with their respective weights: H1 = 0.555; K1 = 0.600; P3 = 0.454; S2 = 0.648; D1 and D2 = 0.425. The selected alternative supplier is PT. X which makes it a priority supplier.